PROVIDING EXPLICIT STRATEGY INSTRUCTION TO ENHANCE STUDENTS’ READING COMPREHENSION AT ENGLISH FOR ISLAMIC STUDIES CLASS - Muzammil, Sa?dulloh; Suhono, Suhono (Smart, 2019)
The aim of research  is to identify the effects and advantages of providing explicit strategy instruction to enhance students? reading comprehension at English for Islamic Studies class of IAIN Pontianak. This was a classroom action research, and its data were collected through reading comprehension test, observation, interview, and document review. Then, the data were analysed though interactive model data analysis. The results showed that, after providing explicit instruction of comprehension strategy, students? reading comprehension improved for they became more strategic and more metacognitive when reading after being introduced with reading comprehension strategy explicitly.